The Politics of Decision Making in the Council of the EU: Explaining Consensus - Sabet, Navid (Politikon: The IAPSS Journal of Political Science, 2015)
This paper examines the decision making of the Council of the European Union to gain insight into how consensus decisions emerge and how they change power allocations and influence the behavior of negotiators and voting blocs. It surveys rationalist and non-rationalist accounts of consensus decisions in the Council and concludes that rationalist explanations are more convincing. In this connection, the central argument of the essay is that consensus emerges as rational negotiators (a) coalesce into blocs dominant enough to win over and suppress opposing coalitions and (b) undertake strategies to avoid blame for failing to win consensus around their own preferred policy.